Establishing correlations in the en-mass migration of dermal fibroblasts on oriented fibrillar scaffolds. (1st October 2015) - Qin, Sisi; Clark, Richard A.F.; Rafailovich, Miriam H.
Graphical abstract: Abstract: Wound healing proceeds via fibroblast migration along three dimensional fibrillar substrates with multiple angles between fibers. We have developed a technique for preparation of three dimensional fibrillar scaffolds with where the fiber diameters and the angles between adjacent fiber layers could be precisely controlled. Using the agarose droplet method we were able to make accurate determinations of the dependence of the migration speed, focal adhesion distribution, and nuclear deformation on the fiber diameter, fiber spacing, and angle between adjacent fiber layers. We found that on oriented single fiber layers, whose diameters exceeded 1 μm, large focal adhesion complexes formed in a linear arrangement along the fiber axis and cell motion was highly correlated. On multi layered scaffolds most of the focal adhesion sites reformed at the junction points and the migration speed was determined by the angle between adjacent fiber layers, which followed a parabolic function with a minimum at 30°. On these surfaces we observed a 25% increase in the number of focal adhesion points and a similar decrease in the degree of nuclear deformation, both phenomena associated with decreased mobility. These results underscore the importance of substrate morphology on the en-mass migration dynamics. Statement of Significance: En-mass fibroblast migration is an essential component of the wound healing process which can determine rate and scar formation. Yet, most publications on this topic have focused on single cell functions. Here we describe a new apparatus where we designed three dimensional fibrillar scaffolds with well controlled angles between junction points and highly oriented fiber geometries. We show that the motion of fibroblasts undergoing en-mass migration on these scaffolds can be controlled by the substrate topography. Significant differences in cell morphology and focal adhesions was found to exist between cells migrating on flat versus fibrillar scaffolds where the migration speed was found to be a function of the angle between fibers, the fiber diameter, and the distance between fibers.